Cognitive mapping of the public's risk perception based on gender and age in Saudi Arabia - Almutairi, Adel F. (2019)
Background: Humans process their lifetime experiences internally as mental images that constitute their cognitive maps, which they employ to recall and assess important features in their relative contexts. This study aims to develop a cognitive map of the public's risk perception based on gender and age in the unique Saudi cultural context. Methods: Data were collected using a self-administered survey measuring the public's perceived risk of nine common life hazards. Differences in gender (bivariate analysis) and age (correlation analysis) over each domain were presented. Cognitive mapping was developed. Results: Of the 317 participants, there were 211 (67.6%) females and 101 (32.4%) males with 32.5 ± 10.7 years as the mean and standard deviation of their age. A series of regression models showed that males had a better perception on the knowledge and control domain compared to females about the hazard of nuclear reactors (β = −0.2, adjusted P < 0.001), yet worse perception on the knowledge and control domain about caffeine intake (β = 0.21, adjusted P < 0.001). Males also had a worse perception of the severity and dread domain in regards to caffeine intake (β = −0.16, adjusted P = 0.005) and pesticides (β = −7.54, adjusted P = 0.002) compared to females, yet females had worse perception of the severity and dread domain concerning bicycles (β = 0.31, adjusted P < 0.001) compared to males. Older study participants had a better perception on the dread and severity domain in regards to caffeine intake (β = −0.26, adjusted P < 0.001) compared to younger participants. Conclusion: Gender and age differences in the risk perception toward some life hazards were observed among Saudi adults, which define the structural features of the Saudi cognitive map.